Perancangan Sistem Kasir Berbasis Web pada Toko Komputer Intechcom untuk Meningkatkan Efisiensi Manajemen Penjualan dan Stok Barang - Bagus Putra Rahadi; Irvan Fauzi; Nila Prawitasari; Wasis Haryono (CV. ITTC INDONESIA, 2024)
The study focuses on designing a web-based cashier system to enhance efficiency in sales and inventory management at Intechcom, a computer and accessories retail store. Using Agile methodology, the study identified the need for automation in transaction recording, real-time stock updates, and integrated reporting. Key features include real-time transaction recording, inventory monitoring, and automated report generation. Initial trials demonstrated significant improvements in operational efficiency and data accuracy. This system is expected to reduce manual errors, improve customer experience, and increase Intechcom's market competitiveness.